2019
DOI: 10.1016/j.fsigen.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

STRmix™ collaborative exercise on DNA mixture interpretation

Abstract: Highlights Inter-laboratory study with 174 participants using STRmix™  CE analysis settings resulted in larger differences in LR than PG software  Differences in log(LR) due to MCMC variation were less than one order of magnitude Abstract (max 400 words)An intra and inter-laboratory study using the probabilistic genotyping (PG) software STRmix™ is reported. Two complex mixtures from the PROVEDIt set, analysed on an Applied Biosystems™ 3500 Series Genetic Analyzer, were selected. 174 participants responded.L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 17 publications
1
52
1
Order By: Relevance
“…In other words, the same examiner, looking at the same pair of fingermarks, will reach a different conclusion 10% of the time [18]. A past study examining the reliability of DNA analyses showed some inconsistency in conclusions [19], and this has recently been replicated by a number of studies showing great variability in DNA results when analyzing the same sample (e.g., some included alleles that were absent, others neglected alleles that were present) further indicating that errors in DNA do exist [20][21][22]. Although DNA analysis is widely regarded as the prevailing standard of forensic science [3], "we do not know any more about human or laboratory error rates in DNA cases than we know about human or laboratory error rates in cases that employ other forensic science techniques" ( [23], p. 3).…”
Section: What Do We Know About Error Rates In Forensic Science?mentioning
confidence: 98%
“…In other words, the same examiner, looking at the same pair of fingermarks, will reach a different conclusion 10% of the time [18]. A past study examining the reliability of DNA analyses showed some inconsistency in conclusions [19], and this has recently been replicated by a number of studies showing great variability in DNA results when analyzing the same sample (e.g., some included alleles that were absent, others neglected alleles that were present) further indicating that errors in DNA do exist [20][21][22]. Although DNA analysis is widely regarded as the prevailing standard of forensic science [3], "we do not know any more about human or laboratory error rates in DNA cases than we know about human or laboratory error rates in cases that employ other forensic science techniques" ( [23], p. 3).…”
Section: What Do We Know About Error Rates In Forensic Science?mentioning
confidence: 98%
“…In their article describing the PROVEDIt data set, the authors express their hope that "a large dataset would play a critical role in demonstrating the foundational validity and robustness of new or existing DNA identity testing technology" (Alfonse et al 2018). Samples from the PROVEDIt data set have been used in PGS comparisons (e.g., Riman et al 2019b) and interlaboratory studies (e.g., Bright et al 2019a). ______________________________________________________________________________________________________ This publication is available free of charge from: https://doi.org/10.6028/NIST.IR.8351-draft…”
Section: Available Research Data Setsmentioning
confidence: 99%
“…As forensic laboratories share their validation summaries and data used for making decisions to enable future independent review of their work, the field has the opportunity to be strengthened. Tables with sample details and LR values have been made available as supplemental files in some publications (e.g., Bright et al 2019a, Rodriguez et al 2019.…”
Section: Comments On Likelihood Ratio Valuesmentioning
confidence: 99%
“…With the generalisation of probabilistic genotyping software, collaborative exercises have been initiated [6,7], guidelines and even standards have been generated (ISFG, For. Reg., SWGDAM).…”
Section: Can Technology Help Towards Consistency Harmonisation and Quality?mentioning
confidence: 99%